Modelisation simplifiee du crash automobile - Moumni, Ziad; Axisa, Fran ois (European Journal of Computational Mechanics, 2000)
In this paper we present a simplified method to model the crashworthiness of vehicles. It is available in the early stages of vehicules design. The aim of our method is to reduce the computing time while preserving accuracy. In our analysis, we use beam elements to represent parts which absorb most of the crash energy. All the nonlinearities (plasticity and contact) are localized in plastic hinges or nonlinear spnngs. For the rigid parts (engine block, transmission parts) we use rigid body solids with 6 degrees of freedom in the space. Finally as the dynamic calculation is concerned, we have chosen a modal approch. The results are compared with those of crashtests. Good agreement is achieved. The computing time is significantly reduced when compared to the models using shell elements.